WORLD GRAIN MARKET IN THE CONTEXT OF NATIONAL AND GLOBAL ASYMMETRIES - KYSIL, Vialiy (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provided the analysis of the systemic, structure-forming nature of the world grain market as a component of the global economy, international trade and as a factor of global economic transformation. The historical, theoretical and institutional context of formation of world grain market, its commodity structure and geographical diversification, as well as the main functional characteristics are considered. It is determined that the world grain market is a strategic element of the global food system, which ensures the redistribution of resources, supports economic stability and affects world trade balances.The impact of geopolitical risks, climate change, digitalization of logistics processes and innovations on the dynamics of the grain market is analyzed. It was proven that increase in its efficiency mainly depends on the development of the infrastructure necessary for grain processing and transportation, comprehensive maintenance of logistics processes, the use of digital technologies and international cooperation. All these aspects determine the role of the grain market as a structural element of the national and world economy.Special attention is paid to the problem of increasing global imbalances and global asymmetry, under which the world grain market requires a solidary regulatory influence. The institutionalization of such influence occurs according to liberal rules, which leads to the formation of market-motivated control centers focused on obtaining a high economic effect. This effect is achieved, in particular, through unfair competition in the global market, and the concentration of managerial power in a number of countries and TNCs. In this regard the article provided recommendations for strengthening the competitiveness and sustainability of the grain sector of the world economy as a structural factor of global trade and sustainable economic growth and also the lever of global management and coordinating influence.
Keywords: global asymmetries; global economic imbalances; national economic strategies; national strategies for ensuring food security; world grain market; global market management; national regulation in market conditions; food security; structural role of the world grain market; grain logistics; grain market infrastructure; institutions of the world grain market; grain export potential; grain market of Ukraine; TNCs and multinational corporations in the grain market